3D optimal defensive guidance strategy with safe distance. (November 2019) - Fang, Feng; Cai, Yuanli; Jabbari, Faryar
This work investigates the active defense problem wherein a target aircraft launches a defending missile (i.e. a defender) to intercept an attacking missile in three-dimensional (3D) space. The novelty of this work includes: adding a safe distance for the target, which protects the target from being influenced by defensive interception, and designing a new 3D defensive guidance strategy without linearization to meet different guidance requirements. The defensive guidance strategy combines the approach of analyzing 3D pursuit-evasion engagement and the optimal control to obtain the guidance law. The approach derives the analytical solutions of 3D pursuit-evasion engagement, and a fast algorithm to predict the trajectory of attacking missile is proposed based on these analytical solutions. The advantages of this guidance strategy include incorporation of the added safe distance requirement directly without hindering the ability of the optimal guidance law to meet other requirements, and straight-forward extension for advanced scenarios where multi-defenders intercept the attacking missile simultaneously from different directions. The performance of the 3D defensive guidance law is evaluated via simulations.